Diseño de la documentación del SG-SST bajo los lineamientos de la Resolución 0312 del 2019 para la empresa Mecánica Industrial A y C S.A.S (2020)
Occupational risks are present in companies and are derived from the activities carried out in them, therefore, it is necessary to develop the identification of these in each area and job position, to then design mitigation and control plans within the possible. This project lands in the case of the company MECÁNICA INDUSTRIAL A Y C S.A.S.